Pαx6 Expression in Postmitotic Neurons Mediates the Growth of Axons in Response to SFRP1 - Sebastián-Serrano, Alvaro; Sandonis, Africa; Cardozo, Marcos; Rodríguez-Tornos, Fernanda M.; Bovolenta, Paola; Nieto, Marta (PLOS ONE, 2012)
During development, the mechanisms that specify neuronal subclasses are coupled to those that determine their axonal response to guidance cues. Pax6 is a homedomain transcription factor required for the specification of a variety of neural precursors. After cell cycle exit, Pax6 expression is often shut down in the precursor progeny and most postmitotic neurons no longer express detectable levels of the protein. There are however exceptions and high Pax6 protein levels are found, for example, in postmitotic retinal ganglion cells (RGCs), dopaminergic neurons of the olfactory bulb and the limbic system in the telencephalon. The function of Pax6 in these differentiating neurons remains mostly elusive. Here, we demonstrate that Pax6 mediates the response of growing axons to SFRP1, a secreted molecule expressed in several Pax6-positive forebrain territories. Forced expression of Pax6 in cultured postmitotic cortical neurons, which do not normally express Pax6, was sufficient to increment axonal length. Growth was blocked by the addition of anti-SFRP1 antibodies, whereas exogenously added SFRP1 increased axonal growth of Pax6-transfected neurons but not that of control or untransfected cortical neurons. In the reverse scenario, shRNA-mediated knock-down of Pax6 in mouse retinal explants specifically abolished RGCs axonal growth induced by SFRP1, but had no effect on RGCs differentiation and it did not modify the effect of Shh or Netrin on axon growth. Taken together these results demonstrate that expression of Pax6 is necessary and sufficient to render postmitotic neurons competent to respond to SFRP1. These results reveal a novel and unexpected function of Pax6 in postmitotic neurons and situate Pax6 and SFRP1 as pair regulators of axonal connectivity.